The pathology of tuberculosis, caused by mycobacterium tuberculosis, in a herd of semi free-ranging springbok (Antidorcas marsupialis) - Williams, J.H. (June Heather) (University of Pretoria, 2013)
Dissertation (MMedVet (Pathology))--University of Pretoria, 2007.